The difficult task of finding the best antihypertensive agent: Comment on “Antihypertensive treatment and development of heart failure in hypertension” - Frankenstein, Lutz (Archives of internal medicine, 2011)
There are a few silent epidemics in medicine, and heart failure certainly is one of them. There are good reasons to care about it: End-stage HF is more deadly than most cancers, and only recently has the idea of HF with preserved ejection fraction been transformed into being accepted as diastolic heart failure. Now diastolic HF is interesting for 2 reasons: (1) it is more common in women—a subgroup notoriously underdiagnosed, undertreated, and underrepresented in clinical trials; and (2) from a global perspective, one of the major risk factors for its development is hypertension and the ensuing hypertensive heart disease. Hypertension, however, does not only lead to diastolic HF but, from a global perspective, it represents the major risk factor for the development of HF as such.